A case of multiple sclerosis mimicking an intracranial mass lesion complicated with obstructive hydrocephalus and brainstem compression - Demir, C. F.; Guler, O.; Tasci, I. (Elsevier Science Bv, 2017)
[Abstract Not Available]
23rd World Congress of Neurology (WCN) -- SEP 16-21, 2017 -- Kyoto, JAPAN